Programas de bolsas de estudo: uma possibilidade de reconhecimento? - Pereira Neto, João Francisco (Universidade do Vale do Rio do Sinos, 2007)
Trough this study, I wish to discuss the process of the emancipation of young people coming from lower social schedules, from the perspective of “The Social Theory of Recognition”, from Axel Honneth. In this sense, it was done a exploratory research, on a case study way and with qualitative characteristics, with ex-students who were beneficiated from the Program of Scholarship from School Methodist Americano, were I looked for evaluating the existing relation between the opportunity of having the Free Studying and the entering in a field of possibilities that turns it possible that this students have their emancipation. In order to realize that, several social field conditions were considered, as well as the economic and cultural basis of the familiar group in the period that this young people received the opportunity, comparing it to the condition they find them self today. Besides, questions related to the development of this people were evaluated, searching to focus, specially, the formation and the reco
Keywords: desigualdades sociais; emancipação; jovens; Teoria Social do Reconhecimento; bolsas de estudo; emancipation; social differences; Social Theory of Recognition; young; program of scholarship; Ciências Sociais Aplicadas